Health QR Code Application in the Novel Containment Strategy and Healthcare Plan for Pregnant Women and Children Under Quarantine During the Summer Outbreak of SARS-CoV-2 Delta Variant in Chengdu, China: An Observational Study - Chen S; Liu T; Li X; Luo Y; Xiao L; Zhang L; Wen R; Lin Y (Dove Medical Press, 2021)
Shan Chen,1,* Tianjiao Liu,1,2,* Xin Li,2,* Yingjuan Luo,3 Li Xiao,1 Libing Zhang,4 Rongkang Wen,3 Yonghong Lin2 1The Medical Administration Department, Chengdu Women's and Children's Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People's Republic of China; 2The Department of Obstetrics and Gynecology, Chengdu Women's and Children's Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People's Republic of China; 3The Healthcare Department, Chengdu Women's and Children's Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People's Republic of China; 4The Department of Pediatric Surgery, Chengdu Women's and Children's Central Hospital, School of Medicine, University of Electronic Science and Technology of China, Chengdu, People's Republic of China*These authors contributed equally to this workCorrespondence: Yonghong Lin Tel +86 13808031895Fax +86 28 61866003Email linyh.2007@aliyun.comPurpose: To report the experience of health QR code application in Chengdu's anti-epidemic measures including circle-layer management, hospital triage system and healthcare plan for quarantined pregnant women and children during the summer outbreak of SARS-CoV-2 Delta strain in 2021 and to evaluate these measures.Methods: We comprehensively summarized Chengdu's health code application in the circle-layer management (a set of stringent confinement measures of places confirmed cases and close contacts have recently been to and less strict quarantine measures of surrounding areas), hospital triage system, and healthcare plan for quarantined pregnant women and children. We also assessed the effectiveness or efficiency of these measures by analyzing the number of different cases with confirmed COVID-19 infections or epidemiological history, the attitude of quarantined pregnant women toward the summer outbreak and healthcare services, as well as the time needed for obtaining epidemiological history and accuracy of health-code-based hospital triage system.Results: The circle-layer management lasted 15 days and ended with no community or nosocomial transmission happened. Approximately 70 pregnant women and 600 children below 6-year-old were quarantined. Four home visits and two patient transfers were performed. Online survey indicated that about 80% of quarantined women felt satisfactory about the healthcare service. The novel triage system identified 137/221 (61.99%) patients with epidemiological history from patients with yellow health code, and 71/4504 (1.57%) patients from patients with green health code in our hospital (p < 0.001). The health QR code markedly outperformed the traditional methods in the efficiency experiment of obtaining epidemiological history (3.52 ± 0.98 vs 78.91 ± 23.18 seconds, P < 0.001).Conclusion: The circle-layer management has successfully and precisely prevented the spread of the summer outbreak of COVID-19 in Chengdu. The health-code-based triage system showed great effectiveness and efficiency in triaging patients with epidemiological history. The healthcare services for quarantined pregnant women has basically met their needs.Keywords: triage, quarantine, pediatrics, obstetrics, precise prevention and control